حق الموظف في العطل والغيابات في التشريع الجزائري - ضريف نسرين (جامعة المسيلة, 2025)
Vaction is a legal right for an employee to take leave from work with permission while retaining all their rights.it is regulated by the Algerian legislator in the Basic law of the civil service (Order03/06),to achieve a balance between employee rights and public service requirements. Vacation aims to provider est and improve conditions, and includes various types such as annual and weekly vacations , holidays,sick leave, maternity leave , and business establishment leave (law22/22).absences are subject to legal principels such as prior justification and proportionality in deductions, and are divided into academic , professional ,social, and exceptional absences. Vacation regulation relies on official and unoffical sources , which enhances job stability and fairnes , and supports efficient job perfomance
Keywords: Legal leave; absences; Ordinance 06-03; civil service; Algerian legislation.